Design and applications of solar sail periodic orbits in the non-autonomous Earth-Moon system - Heiligers, Maria; Macdonald, Malcolm; Parker, Jeffrey S. (2015)
Solar sailing has great potential for a range of high-energy and long duration mis-sions in the Sun-Earth system. This paper extends this potential to the non-autonomous Earth-Moon system through the use of a differential correction scheme, and by selecting suitable in-plane and out-of-plane sail steering laws to develop new families of solar sail libration point orbits that are periodic with the Sun’s motion around the Earth-Moon system. New orbits include those that bifur-cate from the natural Lyapunov, halo and eight-shaped orbit families at the first and second Lagrange points. The potential of these orbits is demonstrated by con-sidering the performance of a subset of orbits for high-latitude Earth observations, lunar far-side communications, and lunar South Pole coverage.